2017
DOI: 10.18311/mvpjms/0/v0/i0/729
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Functional Outcome of Primary Cemented Bipolar Hemiarthroplasty in the Management of Unstable Inter-Trochanteric Fracture of Femur among Elderly

Abstract: Aims and Objectives: To evaluate the results with regard to function, to restoring proper limb length after surgery and to study the associated complications in intertrochanteric fractures treated by cemented bipolar hemiarthroplasty in elderly. Methodology: This is a prospective study of 25 cases of Intertrochanteric fractures admitted to a tertiary care center between August 2013 and November 2015 treated with Cemented Bipolar Hemiarthroplasty for intertrochanteric fractures. Cases were taken according to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…In group B, 9 (30%) patients had excellent outcome. 7,8 The difference among outcome at one year in both groups showed no statistical significance by chi square test. (P>0.05).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In group B, 9 (30%) patients had excellent outcome. 7,8 The difference among outcome at one year in both groups showed no statistical significance by chi square test. (P>0.05).…”
Section: Discussionmentioning
confidence: 91%
“…(P>0.05). 7,8 Narendra Reddy Medagam et al observed the mean HHS at the end of 6 weeks in proximal femoral nails (PFN) group was 73.09 and in coxofemoral bypass group was 77.8. At the end of 6 months, the mean HHS in PFN was 77.38 and in coxofemoral bypass group was 79.85.…”
Section: Discussionmentioning
confidence: 99%
“…(P<0.05) But, at 6 and 9 months both groups shows better outcome with no statistical significant difference. (p>0.05) [7,8] . Narendra Reddy Medagam et al observed the mean HHS at the end of 6 weeks in proximal femoral nails (PFN) group was 73.09 and in coxofemoral bypass group was 77.8.…”
Section: Introductionmentioning
confidence: 83%
“…Out of total 60 patients, 38 were females while 22 patients were male. There was female dominance with 18 (60%) and 20 (66.67%) patients among Group A and Group B respectively [7,8] . There was no gender difference when two groups were compared statistically.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation